Answer: k = 4
Step-by-step explanation:
The linear equation f(x) = x-1 has the y intercept -1. We can see this by comparing it to y = mx+b and see that b = -1. Or we could plug in x = 0 to get the output y = -1.
The graph shows the y intercept is y = 3. The jump from y = -1 to y = 3 is plus 4. This means the graph of f(x) has been moved up 4 units. Therefore, k = 4.
Since y = f(x), saying g(x) = f(x)+k = f(x)+4 means we add 4 onto each y value. This indicates every point on the f(x) line moves up 4 units to arrive at a corresponding point on the g(x) line.